Consumer Preferences For Motor Vehicle Insurance Attributes and Implications For Asuransi Jasindo's Marketing Strategy - Gio Adamartata Girsang; Ujang Sumarwan; Irni Johan (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Intense competition requires companies to develop products that align with consumer preferences. Asuransi Jasindo faces a low market share in the motor vehicle insurance sector, which is poised for growth due to an increasing number of vehicles and a government plan to mandate insurance coverage.Purpose: This study aims to analyze consumer preferences for motor vehicle insurance attributes, determine the most ideal combination of attributes, and formulate strategic implications for Asuransi Jasindo's product development.Design/methodology/approach: This research employs a quantitative approach through Choice-Based Conjoint (CBC) Analysis. Data were collected from a sample of 300 consumer in the Jabodetabek area. Data analysis was conducted by estimating part-worth utility values and relative attribute importance, followed by market simulations using Sawtooth Software.Findings/Result: Claim service is identified as the most influential attribute (38,19%), followed by Additional Services (18,39%) and Price Scheme (16,28%). The ideal product combines a fast claim process with an authorized dealer (ATPM) workshop network, comprehensive additional services including a replacement car, a 25% price discount, and omnichannel service access. Market simulations predict that launching a product with this ideal configuration could increase Asuransi Jasindo's preference share from 10,87% to 33,89%. Conclusion: Consumer preferences in motor vehicle insurance have shifted from a focus on traditional factors like price and brand towards service quality and customer experience. Theoretically, this study enriches the behavioral insurance literature by providing empirical evidence on how regulatory price floors can neutralize price sensitivity, shifting consumer focus towards service quality and 'moment of truth' experiences.Originality/value (State of the art): This study provides data-driven strategic recommendations for a state-owned insurance company to enhance its product competitiveness. Keywords: conjoint analysis, consumer preference, motor vehicle insurance, marketing strategy, product development